2008
DOI: 10.2152/jmi.55.167
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones and immunity

Abstract: : The amount of soy products consumed in Japan is much greater than that in Western countries. Recent evidence indicates that soy isoflavones play a beneficial role in obesity, cancer, osteoporosis, and cardiovascular disease. The soybean isoflavone genistein is present at high levels in soy products. Genistein is structurally similar to 17! -estradiol (E2), and genistein has been suggested to be act as E2 or an antagonist against E2. Genistein suppresses antigen-specific immune response in vivo and lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 37 publications
1
105
0
6
Order By: Relevance
“…In contrast, two reports did not confirm the extensive immune abnormalities described previously and reported that a number of parameters related to immune cell populations were within the normal range in soy-fed infants [20,21]. Phytoestrogen and some of their metabolites may affect allergic responses via the enhancement of IL-4 production in T cells [22]. The functions of T cells and NK cells were altered after oral exposure to genistein at physiologically relevant concentrations in experimental animals.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, two reports did not confirm the extensive immune abnormalities described previously and reported that a number of parameters related to immune cell populations were within the normal range in soy-fed infants [20,21]. Phytoestrogen and some of their metabolites may affect allergic responses via the enhancement of IL-4 production in T cells [22]. The functions of T cells and NK cells were altered after oral exposure to genistein at physiologically relevant concentrations in experimental animals.…”
Section: Discussionmentioning
confidence: 77%
“…In support, the present data showed increased NO level in OVX rats fed SbO or SO supplemented diets. This observation may be attributed to the fact that phytoestrogens in the diet may have a role in modulating hormone related disease based on their ability to elicit estrogenic activity (Sakai and Kogiso 2008). Estrogen increases the production of NO by enhancing endothelial NO synthase activity (Sasaki et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important legumes species, soybean contains about 40% highly nutritious protein with all essential amino acids, rich in magnesium, phospholipids, vitamins and minerals [2][3] and also contains secondary metabolites such as isoflavones [4], saponins, phyticacid, oligosaccharides [4] and phytoestrogens [5] which are beneficial to health. In addition to its nutritional values, soybean is also used as important nitrogen (N 2 )-fixing crop throughout the world for the restoration and maintenance of soil fertility in a sustainable way and consequently the improvement of crop yields [6][7] Demand for soybean in Indonesia continues to increase, along with increasing public knowledge of the benefits of soy as a functional food.…”
Section: Introductionmentioning
confidence: 99%